Estudo comparativo entre a subvenção econômica à inovação operada pela Finep e programas correlatos de subsídio em países desenvolvidos - Andrade, Alexandre Zuccolo Barragat de (2009)
Technology Innovation is one of the main competitive factors of modern economies and is object of public policy in every developed country. In Brazil, Finep has been providing support to the technology development of firms since 1976. Starting from 2006, it also began to offer direct subsidies in the form of economic subventions. This study characterizes the concept of economic subvention according to Brazilian Law, presenting examples of its uses as public policies, and specifically the economic subvention for innovation as operated by Finep from 2006 to 2009. Then, Finep's subvention practice is compared, by content analysis, with related subsidies in developed countries. For such, the North American programs SBIR, ATP and TIP, and the programs operated by OSEO in France and CDTI in Spain were selected. Aspects related to the logics of intervention are approached, notably technology risk, government subsidies share, institutional models and instruments integration.